Circulating interleukin-1 receptor antagonist (IL-1RA) serum levels in patients undergoing orthotopic heart transplantation - Thiele, Rudolf; Daniel, Volker; Opelz, Gerhard; Lange, Rüdiger; Sack, Falk-Udo; Jakob, Heinz; Hagl, Siegfried (Transplant international, 1998)
In a pilot study we determined the serum levels of circulating interleukin-1 receptor antagonist (IL-1ra) in patients undergoing orthotopic heart transplantation and in control patients scheduled for open heart surgery without allograft transplantation. Blood samples were obtained from 12 transplant recipients and 7 controls prior to the operative procedures to determine baseline values. Serum levels of IL-1ra were measured within 12 h of decrossclamping of the aorta and every 24 h for the following 14 days. Endomyocardial biopsies were obtained weekly for the 1st month after transplantation. Compared to baseline values, IL-1ra serum levels 12 h after decrossclamping of the aorta were significantly higher both in the control group (507 ± 165 vs 3980 ± 452 pg/ml, P < 0.01) and among the transplant recipients (413 ± 180 vs 4117 ± 459 pg/ml, P < 0.01) IL-1ra levels remained significantly elevated for 2 and 5 days, respectively. There were no significant differences in the IL-1ra serum levels between the two groups throughout the observation period. Endomyocardial biopsies of two patients showed acute allograft rejection, Billingham grade IIIa and IIIb, respectively. In both cases, the rejection episodes were accompanied by a renewed and more pronounced elevation in the IL-1ra serum levels beyond 4000 pg/ml for at least 2 days. These preliminary results indicate that IL-1ra may be a nonspecific immune marker during the first few days after orthotopic heart transplantation and cardiopulmonary bypass. Moreover, renewed, prolonged increases in IL-1ra appear to be associated with rejection. Further studies are needed to confirm the predictive value of IL-1ra in the detection of acute allograft rejection.